Combinatorial Fine‐Tuning of GNA1 and GlmS Expression by 5'‐Terminus Fusion Engineering Leads to Overproduction of N‐Acetylglucosamine in Bacillus subtilis. Issue 3 (4th September 2018) - Ma, Wenlong; Liu, Yanfeng; Wang, Yue; Lv, Xueqin; Li, Jianghua; Du, Guocheng; Liu, Long
Abstract : Glucosamine‐6‐phosphate N‐acetyltransferase (GNA1) that catalyzes acetyl transfer from acetyl‐coenzyme A to glucosamine‐6‐phosphate (GlcN‐6P), and glutamine‐fructose‐6‐phosphate aminotransferase (GlmS) that catalyzes the formation of GlcN‐6P from fructose‐6‐phosphate (Fru‐6P), are two key enzymes in Bacillus subtilis for the bioproduction of N‐acetylglucosamine (GlcNAc), a nutraceutical that has various applications in healthcare. In this study, the expression of GNA1 and GlmS is fine‐tuned by 5'‐terminus fusion engineering to improve GlcNAc production. Specifically, the expression level of GNA1 is enhanced at the translational level via fusion of an epitope tag to the 5'‐terminus of GNA1 gene and ribosome binding site (RBS) sequence engineering. Next, enhanced expression of GlmS is achieved at the transcriptional and translational levels by fusing an mRNA stabilizer to the 5'‐terminus of GlmS gene. Under the control of GNA1 (fusion with cMyc tag and with the optimum RBS M‐Rm) and GlmS (fusion with mRNA stabilizer Δ ermC +14/7A), the GlcNAc titer and yield in the shake flask increase to 18.5 g L −1 and 0.37 g GlcNAc/g glucose, which are 2.9‐fold and 2.3‐fold that of the control, respectively. This synthetic pathway fine‐tuning method at the transcriptional and translational levels by combinatorial modulation of regulatory elements, including epitope tag, RBS sequence, and mRNA stabilizer, might represent a general and effective approach for the construction of microbial cell factories. Abstract : Blocking overflow metabolism of acetate and acetoin in recombinant Bacillus subtilis results in accumulation of pyruvate. In this study, carbon flux is successfully diverted from pyruvate to the GlcNAc synthetic pathway by combinatorial fine‐tuning expression of GNA1 and GlmS, and promoted GlcNAc production.